Study on the rooting promotion of chrysanthemum cuttings by Massilia consociata KC 009 - Lu, Chunmei; Dong, Haotian; Jiao, Yu; Muhammad, Murad; Yang, Yuanchun; Zhang, Jing; Liu, Rui; Cao, Yanru (Frontiers in Plant Science, 2025)
Continuous cropping reduces the rooting rate and quality of chrysanthemum cuttings, negatively impacting the development of the chrysanthemum industry. This study provides the first evidence that Massilia consociata enhances root formation in chrysanthemum cuttings. Using pot experiments, combined with physiological indicator measurements and analysis of the endophytic microbial composition of the chrysanthemum cuttings, the mechanism promoting the rooting effect was investigated. After 106 CFU/mL of KC 009 fermentation was applied to chrysanthemum cuttings for 21 days, the rooting rate, root number, root length and root dry weight significantly increased by 28.97%-50% (p < 0.01). Some physiological indicators such as soluble protein, soluble sugar, chlorophyll and indole-3-acetic acid (IAA) were significantly enhanced. Correlation analysis between rooting and physiological indicators revealed that soluble protein was the most critical physiological factor contributing to root formation. The results of high-throughput sequencing of rhizosphere and endophytic microorganisms in chrysanthemum cuttings showed that KC 009 significantly reduced the richness and diversity of endophytic microorganisms. The dominant endophytic bacteria changed from Ochrobactrum to Chryseobacterium and Alcaligenes, which could produce IAA and enhance plant stress resistance. Spearman correlation analysis showed that Chryseobacterium was significantly positively correlated with soluble protein, starch, and chlorophyll, and Alcaligenes was positively correlated with PPO, POD, and soluble sugar. The abundance of Cladosporium, a potential pathogen in endophytic fungi, decreased by 16.70% (p < 0.05). Mantel test analysis indicated that soluble protein and starch were most closely related to the endophytic bacterial and fungal communities of chrysanthemum, respectively. Functional prediction of endophytic bacteria revealed that the abundance of 14 metabolic pathways related to plant growth was significantly increased. This study provides theoretical and practical references for promoting the rooting of chrysanthemum cuttings, holding significant importance for the development of the chrysanthemum industry.